FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN K4 DI KECAMATAN KARIMUN KABUPATEN KARIMUN - Sari, Yuliana; Suryanti, Suryanti (Universitas Batam, 2019)
The coverage of K1 Visit in Indonesia is on 97.5%, and Achievement of K4 is on 87.48%. In this case, it is still less than the national target of K1 visit which is 100%, and K4 visit which is 95%. This research is quantitative research with Cross-Sectional design. The study was conducted from June to August with accidental sampling method of 42 respondents. Respondents were mostly categorized as multipara, which is 32 respondents (76.2%), did not receive husband support (76.2%), and did not make K4 visits (78.6%). There was a correlation between respondents' knowledge and K4 visits in Karimun District, Karimun Regency Year 2017 with p-value = 0,017, there is a relationship between parity with K4 visit in Karimun District Karimun Regency Year 2017 with p-value = 0,012. And there is a relationship between husband support with K4 visit in Karimun District Karimun Regency Year 2017 with p-value = 0,012. So it can be concluded that there is a relationship between knowledge with K4 visit, there is relationship between parity with K4 visit, and there is a relationship between husband supports with K4, for respondents who want to do K4 visit.